(untitled) (Jurnal Bahasa, 2003)
Previous studies of adult bilinguals have shown that cognates (translation equivalents similar in sound and spelling) are translated faster than non-cognates and different representations for the two categories in bilingual memory have been suggested (Kroll and Stewart, 1994, van Hell and de Groot, 1998). Assuming that bilingual children’s representations are similar to those of adults, effects of form similarity between words should also be observed. This paper examines form-similar nouns in the early lexical development of a bilingual Germani English child aged 1; 11-2;9 as well as effects of form similarity in picture naming and translation in two groups of German/English children age 8-9. Form similarity here differs from cognate status of a word in that it implies similarity in sound only. Considering the way hearing children acquire words, it seem necessary to restrict the similarity of words to this modality. Similarly, the presentation of items in translation task was auditory. The results show an effect of form similarity in early lexical development, whereby form-similar words occurred frequently in the beginning of the observation period in both languages and were more likely to have a translation equivalent in the child’s English. In the translation task, form similarity resulted in lower latencies for both language directions. The results thereby confirm that form similarity affects representations in both adult and child learners.